Characterisation of kenaf fibre composite trapezoid sandwich structure based on corrugated core - Ahmad Fahmy, Jusoh (2020)
Natural fibre reinforced composites have been widely used since ancient times. Natural fibre includes all form of fibre from grass, seeds, woody plants, fruits, wild plants, agricultural crop, aquatic plants, palm plants, leaves, animal hair, and its bark. Some of the advantages of natural fibre are very environmentally friendly, can be completely biodegradable, non-toxic and a source of income for rural and agricultural communities. Kenaf is a natural fibre that a promising mechanical performance in comparison with other natural fibres. Sandwich panels are becoming increasingly important materials because of their multipurpose uses in various industrial sectors. One of their best features is their high-stiffness-to-mass ratio, particularly under bending conditions. In this experiment, trapezoidal corrugated cores using short kenaf fibre were manufactured in order to investigate the effect of chemical treatment on kenaf fibre to the performance of kenaf/epoxy corrugated composites and to study the effect of varying the parameters and properties of kenaf/epoxy corrugated cores sandwich structure. The corrugated core was prepared using kenaf natural fibre and liquid epoxy resin as its matrix material along with a hardener (2 epoxy: I hardener by weight%). The fibre thickness was set at 4 mm, 6 mm and 12 mm with 5%, 10% and 15% fibre weight percentage, respectively. For the 12 mm sample, an additional mercerisation process was done. The mould used for the corrugation of the composite material was fabricated from a steel block of 290 mm in length, 210 mm in width and 24 mm in thickness for both male and female moulds. The mould was intentionally prepared to have a corrugated slope with a 45° angle to produce corrugated-end products. The fully cured sample was cut into single units of 50 mm x 25mm dimensions and static tension and compression tests were carried out. For the 12 mm samples, the kenaf fibres were treated with a 5% alkaline solution (NaOH) in a weight ratio of 1 fibre:20 NaOH. As a result the tensile and compression tests significantly increased in value. The highest stress value for treated kenaf fibre was recorded at 5.88 MPa, which was 18% higher than the untreated kenaf fibre. The same behavioural results were found in the compression test where the highest recorded stress value for treated kenaf fibre was 6.96 MPa; whereas the highest recorded stress for untreated kenaf fibre was only 5.30 MPa. It shows that the chemical treatment using a 5% solution did affect the mechanical performance of the kenaf fibre composite. In the 4 mm tensile test, a lower stress value was recorded at 2.07 MPa (from sample KEU.4.5) and the stress increased to 3.49 MPa for the 6 mm samples (KEU .6.15) as the fibre content also increased from 5% to 15% by weight. Meanwhile, for the compression test, the 12 mm samples with 15% fibre had a stress value of 5.30 MPa which was higher than the 6 mm samples with the same fibre loading (3. 72 MPa). It clearly shows that the increment in sample thickness and fibre loading resulted in the increment of stress limits for both tensile and compression tests. iv